PENGARUH BUDAYA ORGANISASI DAN LINGKUNGAN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PERUM BULOG DIVRE JAWA BARAT - Ade Rista Yunita; Romat Saragih (Jurnal Ilmiah MEA (Manajemen, Ekonomi, & Akuntansi), 2019)
As one of the state-owned companies engaged in logistics, Perum BULOG Divre Jawa Barat always needs high-quality human resources with high work productivity in order to achieve the company's goals. In increasing work productivity, organizational culture and work environment is one of the factors to increase the productivity of Perum BULOG Divre Jabar. This study was conducted to determine the effect of organizational culture and work environment on the work productivity of Perum BULOG Divre Jabar. The purpose of this study is to find out and analyze how the level of employee productivity, organizational culture and work environment and to know and analyze how the influence of organizational culture and work environment partially and simultaneously on employee work productivity. This type of research uses descriptive and causal analysis. The research method used is a quantitative method. In this study using a sample of 69 employees of Perum BULOG Divre Jabar. The method used is quantitative by processing research data using multiple linear regression to determine the level of relationships between variables partially or simultaneously. The results of the study show that work productivity, organizational culture and work environment are currently classified as good. Then for organizational culture variables have a partial and significant effect that is proven through the results of hypothesis testing (t-test) where t count> t table (6.557> 1.668) and a significant value <5%. In addition, the work environment also has a partial and significant effect as evidenced by the results of hypothesis testing (t-test) where t count> t table (3.807> 1.668) and significant value <5%. Then the organizational culture and simultaneous work environment towards work productivity are proven through the results of hypothesis testing (f test) where F count> F table (142,287> 3.14).